Does short-term high dose probiotic supplementation containing Lactobacillus casei attenuate exertional-heat stress induced endotoxaemia and cytokinaemia? - Gill, S. K.; Allerton, D. M.; Ansley-Robson, P.; Hemmings, K.; Cox, M.; Costa, R. J. S. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
The study aimed to determine if short-term high dose probiotic supplementation containing Lactobacillus casei (L.casei) attenuates the commonly reported exertional-heat stress (EHS) induced endotoxinaemia and cytokinaemia. Eight endurance trained male volunteers (mean± SD: age 26 ± 6 y, nude body mass 70.2 ± 8.8 kg, height 1.75 ± 0.05 m, VO2max 59 ± 5 ml·kg-1·min-1) completed a blinded randomized cross-over design, whereby oral ingestion of a commercially available probiotic beverage containing L.casei (volume equivalent for ×1011 colony forming units·day-1) (PRO) or placebo (PLA) was consumed for 7 consecutive days before exposure to EHS, which comprised of 2h running exercise at 60% VO2max in hot ambient conditions (34.0 °C and 32% RH). Blood samples were collected at baseline (7 days before EHS), pre-EHS, post-EHS (1 hr, 2 hr, 4 hr, and at 24 hr). Plasma samples were analyzed for gram-negative bacterial endotoxin, cytokine profile (IL-6, IL-1ß, TNF-alpha, IFN-gamma, IL-8, and IL-10) and plasma osmolality. Plasma osmolality did not differ between trials. Seven days of L.casei supplementation did not show significant changes in resting circulatory endotoxin concentration or plasma cytokine profile compared with PLA. A main effect of time was observed for IL-6, TNF-alpha, IL-10 and IL-8; whereby levels increased in response to EHS (p < .05). Relative to pre-EHS concentrations, higher plasma concentrations of endotoxin (p = .05), and a trend for higher plasma TNF-alpha concentration (p = .09) was observed on PRO compared with PLA throughout recovery. Short-term high dose supplementation of a probiotic beverage containing L.casei before EHS did not attenuate EHS induced endotoxaemia and cytokinaemia; nor is it more positively favorable over a placebo.